Profiles in corruption ebook Abuse of power by america's progressive elite. - Schweizer, Peter (2020)
NEW YORK TIMES BESTSELLER! Washington insiders operate by a proven credo: When a Peter Schweizer book drops, duck and brace for impact. For over a decade, the work of six-time New York Times bestselling investigative reporter Peter Schweizer has sent shockwaves through the political universe. Clinton Cash revealed the Clintons' international money flow, exposed global corruption, and sparked an FBI investigation. Secret Empires exposed bipartisan corruption and launched congressional investigations. And Throw Them All Out and Extortion prompted passage of the STOCK Act. Indeed, Schweizer's "follow the money" bombshell revelations have been featured on the front pages of the New York Times and the Wall Street Journal, and regularly appear on national news programs, including 60 Minutes. Now Schweizer and his team of seasoned investigators turn their focus to the nation's top progressives—politicians who strive to acquire more government power to achieve their political ends. Can they be trusted with more power? In Profiles in Corruption, Schweizer offers a deep-dive investigation into the private finances, and secrets deals of some of America's top political leaders. And, as usual, he doesn't disappoint, with never-before-reported revelations that uncover corruption and abuse of power—all backed up by a mountain of corporate documents and legal filings from around the globe. Learn about how they are making sweetheart deals, generating side income, bending the law to their own benefits, using legislation to advance their own interests, and much more. Profiles in Corruption contains tomorrow's headlines.